The Influence of Papercraft on Early Childhood Cutting Ability - Jannah, Icuk Nur; Pradana, Pascalian Hadi; Kurniawan, Nurhafit (FKIP Universitas Halu Oleo, 2024)
Early childhood education is a form of education aimed at optimizing children's growth and development. The purpose of this research is to determine the effect of papercraft on the cutting skills of young children. This research uses an experimental research design. Experimental research in education is a research activity aimed at evaluating the effects of educational treatments on children's behavior or testing the hypothesis of whether or not there is an influence of handicrafts on children's cutting skills. The design used is a one-group pretest-posttest design. Based on the research results, the significance value of p is 0.003 <0.05, thus H0 is accepted, indicating that there is a significant effect on the cutting skills of children between the pretest and posttest at TK Nurus Sa'adah 03. From the results of the Wilcoxon test, which showed that there was no decline in cutting skills. In the positive range, there is an improvement from pre-test to post-test. This improvement can be seen in the similarity between the pretest and posttest, with 1 child showing neither improvement nor decline. Therefore, there are 11 children whose cutting skills improved through the papercraft activities.